Dengue Virus Serotype 2 from a Sylvatic Lineage Isolated from a Patient with Dengue Hemorrhagic Fever - Cardosa, Mary Jane; Mong, How Ooi; Phaik, Hooi Tio; David, Perera; Holmes, Edward C.; Khatijar, Bibi; Zahara, Abd Manap (PLOS, 2009)
Dengue viruses circulate in both human and sylvatic cycles. Although dengue viruses (DENV) infecting humans can cause major epidemics and severe disease, relatively little is known about the epidemiology and etiology of sylvatic dengue viruses. A 20-year-old male developed dengue hemorrhagic fever (DHF) with thrombocytopenia (12,000/ul) and a raise hematocrit (29.5% above baseline) in January 2008 in Malaysia. Dengue virus serotype 2 was isolated from his blood on day 4 of fever. A phylogenetic analysis of the complete genome sequence revealed that this virus was a member of a sylvatic lineage of DENV-2 and most closely related to a virus isolated from a sentinel monkey in Malaysia in 1970. This is the first identification of a sylvatic DENV circulating in Asia since 1975.